Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5423/ppj.nt.02.2014.0015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of a Natural Population of Apple stem pitting virus Isolated from Apple in Korea

Abstract: Apple stem pitting virus (ASPV), of the Foveavirus genus in the family Betaflexiviridae, is one of the most common viruses of apple and pear trees. To examine variability of the coat protein (CP) gene from ASPV, eight isolates originating from 251 apple trees, which were collected from 22 apple orchards located in intensive apple growing areas of the North Gyeongsang and North Jeolla Provinces in Korea, were sequenced and compared. The nucleotide sequence identity of the CP gene of eight ASPV isolates ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
4
20
0
2
Order By: Relevance
“…It has been shown that all five genes encoded by ASPV had large genetic variability, especially in the CP-encoding ORF5. The CP gene is one of the most commonly used markers for evolutionary analyses of viruses in the Betaflexiviridae family [11][12][13] as well as for other plant viruses [14][15][16][17][18]. Previous studies about the genetic diversity of ASPV isolates have shown that the nucleotide identity among CP sequences was high, though with a certain degree of discrepancy among studies: between 81.7-99.3 % [4], 64.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that all five genes encoded by ASPV had large genetic variability, especially in the CP-encoding ORF5. The CP gene is one of the most commonly used markers for evolutionary analyses of viruses in the Betaflexiviridae family [11][12][13] as well as for other plant viruses [14][15][16][17][18]. Previous studies about the genetic diversity of ASPV isolates have shown that the nucleotide identity among CP sequences was high, though with a certain degree of discrepancy among studies: between 81.7-99.3 % [4], 64.…”
Section: Introductionmentioning
confidence: 99%
“…Here, population genetic analysis of PVX isolates from different countries was done based on the CP sequences because conserved nature of the CP gene makes it a suitable candidate for such studies. The CP gene in plant viruses is commonly used for investigation on genetic variation and molecular evolution [10,27,41,43] and was therefore selected for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Эти вирусы распространены как в соседних с Беларусью странах (Poniedziałek et al, 2001;PaduchCichal et al, 2005;Gospodaryk et al, 2008;Pūpola et al, 2011;Сироткин, 2012;Stankienė et al, 2012;Yoon et al, 2014), так и в географически удаленных от нее (German мест, где они были выделены, и таким образом проследить направление их распространения. С одной стороны, бело-русский изолят ACLSV оказался близок трем изолятам из граничащей с ней Литвы (см.…”
Section: Discussionunclassified
“…Исследования, проведенные в разных странах, свидетельствуют о доминировании от-рицательной селекции в эволюции вирусов, поражающих яблоню. Однако отдельные нуклеотиды или регионы ге-номов вирусов могут находиться под влиянием положи-тельной селекции (Komorowska et al, 2011;Liebenberg et al, 2012;Liu et al, 2014;Yoon et al, 2014). Возможно, такое селективное давление обусловлено участием одного вирусного белка в множестве процессов.…”
unclassified